2024
DOI: 10.1093/plphys/kiae169
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric mutations in grapevine ENHANCED DISEASE RESISTANCE1 improve resistance to powdery mildew without growth penalty

Xue-Na Yu,
Ye Guo,
Qianling Yang
et al.

Abstract: Grapevine (Vitis vinifera L.) incurs severequality degradation and yield loss from powdery mildew, a major fungal disease caused by Erysiphe necator. ENHANCED DISEASE RESISTANCE1 (EDR1), a Raf-like mitogen-activated protein kinase kinase kinase (MAPKKK), negatively regulates defense responses against powdery mildew in Arabidopsis (Arabidopsis thaliana). However, little is known about the role of the putatively orthologous EDR1 gene in grapevine. In this study, we obtained grapevine VviEDR1-edited lines using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In this issue of Plant Physiology , Yu et al (2024) identified an ortholog of the Arabidopsis EDR1 gene in grapevine ( VviEDR1 ) through multiple sequence alignment and phylogenetic analysis. Expression analysis in susceptible Thompson Seedless grapevine leaves suggests continual downregulation of VviEDR1 after E. necator inoculation, indicating the role of VviEDR1 in grapevine powdery mildew infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Plant Physiology , Yu et al (2024) identified an ortholog of the Arabidopsis EDR1 gene in grapevine ( VviEDR1 ) through multiple sequence alignment and phylogenetic analysis. Expression analysis in susceptible Thompson Seedless grapevine leaves suggests continual downregulation of VviEDR1 after E. necator inoculation, indicating the role of VviEDR1 in grapevine powdery mildew infection.…”
mentioning
confidence: 99%
“… Schematic model depicting how VviEDR1-chi lines enhance resistance to powdery mildew without compromising growth (Figure 8 of Yu et al 2024 ). The VviEDR1-chi lines express both the wild-type VviEDR1 and mutant Vviedr1 alleles as chimera ( VviEDR1-chi ), ensuring the dynamic stability of the VviEDR1 mutation.…”
mentioning
confidence: 99%